Geoinformatics Applications to Spatial Relation Assessment of Land Use and Water Quality in the Prasae Watershed, Rayong Province - Intacharoen, Prasarn; Thaipichitburapha, Patrawut; Buranapratheprat , Anukul; Na-u-dom, Tawatchai (Recent Science and Technology, 2021)
Geoinformatics technology was used to study land use changes and the linkage to the water qualities in the lower of Prasae watershed. The obtained results could support the decision maker for spatial management. Three aims of this research are; 1) to evaluate the land use changes in the Prasae watershed, 2) to analyze the spatial relationship of land use and water qualities in the lower Prasae watershed area and 3) to developed the spatial model base on land use and water qualities changes in the lower Prasae watershed. Spatial classification of land use type base on Landsat satellite imageries were classified as vegetation area, community/build-up area, water area, and bare land area. Results showed that, overall accuracy was showed more than 88%, Kappa coefficient was 0.77. Correlation analysis of water qualities base on five of nutrient’s parameters are showed that highest of correlation coefficient to community/build-up area. Moreover, amount of organic matter in the water source and land use as follows: nitrite-nitrogen (NO2-N) = -0.269- 0.0474(Vegetation) - 0.256(Water) + 0.449(Bare-land); (R2= 0.91). CA-Markov Chain model was applied to study land use changes, and it was found that land use changes in the next 5 years would be more obvious in 2003 because of the urbanization. In addition, it was found that the most stable activity was the vegetable and water area, because an aquaculture activity in the coastal zone do not increase. While, opportunity of the community/build-up will be a lot of changes as well.